Fault-tolerant single-input dual-output converter with preserved output under fault operation - Bharathi, Botta Venkata Vara Lova Kala; Satish, Raavi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
DC-DC converters have played an important role in the auxiliary power supply to electric vehicles, DC micro-grids, and portable electronic applications. To reduce the number of components and to improve the power density, multiport DC-DC converters have been recently proposed. Many multi-output converters are designed based on specific operational constraints on duty ratio or inductor currents. Further, simultaneous control of outputs is critical and involves cross-regulation issues. This paper proposes a single-input dual-output (SIDO) DC-DC converter with fault-tolerant circuit configuration to circumvent these challenges. The designed converter is helpful for the simultaneous control of loads by cross-regulation issues and has simple control without any control constraints on duty ratio or inductor currents. The topology proposed in this paper, can most significantly tolerate the failure during open-circuit for single and multiple switches and gives the preserved output voltage under fault case. The effectiveness and feasibility of the proposed configuration is validated using MATLAB/Simulink.